Identity Statuses Among Juvenile delinquents in Jordan - Banat, Suhaila Mahmoud (Journal of Educational and Psychological Sciences, 2022)
The study aimed to identify the identity statuses of juvenile delinquents who suffer from drug abuse in Jordan. The sample consisted of (75) male juveniles in Jordan who abuse drugs, and the identity statuses scale consisting of (26) items was applied to them after extracting its validity and reliability. After conducting statistical analyses, the results indicated that the delayed identity status was the most common among the study sample, while the closed identity was the least common. The results also showed that there were no differences in identity statuses due to the variable of birth order and monthly income, with the exception of the difussion identity status, and the differences came in favor of those with low incomes (less than 500 dinars). In light of the results of the study, the researcher recommends conducting more surveys, qualitative and experimental studies on juveniles who suffer from drug abuse.
Keywords: identity statuses; juvenile delinquents; drug abuse